2018
DOI: 10.1038/s41379-018-0090-y
|View full text |Cite
|
Sign up to set email alerts
|

HPV RNA CISH score identifies two prognostic groups in a p16 positive oropharyngeal squamous cell carcinoma population

Abstract: HPV-related and HPV-unrelated oropharyngeal squamous cell carcinomas are two distinct entities according to the Union for International Cancer Control, with a better prognosis conferred to HPV-related oropharyngeal squamous cell carcinomas. However, variable clinical outcomes are observed among patients with p16 positive oropharyngeal squamous cell carcinoma, which is a surrogate marker of HPV infection. We aimed to investigate the prognostic value of RNA CISH against E6 and E7 transcripts (HPV RNA CISH) to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
9
1
2
Order By: Relevance
“…The inclusion of this additional quality control measure may also explain why there were no p16−RNAISH+ cases in our cohort, an observation reported in studies utilizing magnification‐based interpretation methods alone 19,20 . Nevertheless, further work is required to define low‐end RNA ISH signal threshold cut‐offs validated against qRT‐PCR reference standards and clinical outcomes 29 …”
Section: Discussionmentioning
confidence: 88%
“…The inclusion of this additional quality control measure may also explain why there were no p16−RNAISH+ cases in our cohort, an observation reported in studies utilizing magnification‐based interpretation methods alone 19,20 . Nevertheless, further work is required to define low‐end RNA ISH signal threshold cut‐offs validated against qRT‐PCR reference standards and clinical outcomes 29 …”
Section: Discussionmentioning
confidence: 88%
“…Our study revealed 15 cases with p16 IHC positivity but HPV-mRNA ISH negativity. Patients with a discordant (p16 IHC+/HPV-) tumor have been related to significantly worse prognosis compared with patients who has a confirmed HPV-positive (p16 IHC+/HPV+) tumor [9,33]. Thus, the use of p16 IHC as a stand-alone test for HPV detection can mislead diagnostics and treatment approaches, particularly when considering treatment deescalation [9].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The binding of DNA cis-acting elements activates transcription of p16 gene, resulting in high activation of p16 protein. 15 The expression level of p16 and Ki-67 is increased, which causes cell cycle disorder and causes cell malignant transformation. Recent studies have shown that E6 and E7 can also bind to other proteins, such as Bak and p21, leading to their genetic instability.…”
Section: Introductionmentioning
confidence: 99%